Structural design optimization of roof slab of a pool type sodium cooled fast reactor. (December 2016) - Prabhu Raja, V; Ramu, M; Thyla, P R; Aithal, Sriramachandra; Rajan Babu, V; Chellapandi, P
Highlights: An approach to predict the structural integrity of relatively complex structures subjected to different loading conditions has been presented. A computationally effective methodology for design optimization named 'metamodel based design optimization' has been discussed. The structural integrity has been assessed for the roof slab of nuclear reactor subjected to dynamic loads including seismic loading conditions. FEA based approach for response spectrum analysis for evaluation of seismic behavior of complex structures has been highlighted. Abstract: The roof slab of the nuclear reactor supports all the components of the reactor. Roof slab is essentially a box structure with top and bottom plates interconnected by vertical shells and radial stiffeners welded to them. The gap between the top and bottom plates is filled with concrete that provides biological and thermal shielding in the top axial direction of the reactor. The 500 MWe Prototype Fast Breeder Reactor (PFBR) is designed based on the Operating Basis Earthquake (OBE) and Safe Shutdown Earthquake (SSE) which are categorized under level A and level D loadings respectively. The primary objective of this work is to optimize the design of the roof slab and to predict and ascertain the structural integrity of the optimized roof slab under static, harmonic and seismic loading conditions. Regression models for critical design parameters are developed and are used in the optimization algorithm.